Modelling the factors associated with quality of life in women with osteoporosis: A cross-sectional study - Rahmatollah Moradzadeh; Maryam Zamanian; Maliheh Taheri (Global Epidemiology)
Background: Considering the important factors contributing to different health-related quality of life (HRQoL) subscales is essential for implementing preventive measures to increase the HRQoL among women with osteoporosis. We here evaluated the variables related to the mental and physical HRQoL in a sample of Iranian osteoporotic women. Methods: In this cross-sectional study, the participants included 111 women with osteoporosis in 2013. Physical and mental of HRQoL were measured by the ECOS-16 questionnaire. Other variables included BMD t-score (Osteoporosis was diagnosed based on bone mineral density (BMD) with BMD t-score < −2.5), age, body mass index, educational level, marital status, duration of the disease, history of bone fracture in the past year, the number of pregnancies, and weekly walking hours. Final regression coefficients were obtained based on the total effects of estimations (decompositions of effects into direct, indirect and total effects) by structural equation model (SEM) analysis. Results: The mean scores of physical and mental domains of HRQoL were 54(21) and 54(25), respectively. The mean of BMD t-score was −3.2 (0.9). Based on the regression coefficients obtained in the SEM model, weekly walking hours(2.2), number of pregnancies (−1.2), and history of bone fracture in past year(−2.9) were the more important determinants of physical aspect of HRQoL than other included variables of this study. Furthermore, age over than 60 (−9.1), history of bone fracture in past year(−4.8), weekly walking hours(2.3), marital status(−5), and education level (3.9)influenced the mental aspect of HRQoL. Conclusions: Social and life style factors tend to impact on physical and mental domains of HRQoL, a measure that is influenced by multiple factors among postmenopausal women. In this respect, these obtained factors should be considered for health planning to improve the physical and mental domains of HRQoL among postmenopausal women.